A Computational Method of Investigating Natural Substances from Cyperus rotundus L. as Potential Brown Planthopper Nilaparvata lugens (Stål) Acetylcholinesterase Inhibitors - Bangash, Saqib Hussain; Wei, Chen-Yang; Ali, Akbar; Ibrahim, Muhammad; Li, Fan-Dan; Hussain, Amjad; Tang, Wen-Wei (Indonesian Journal of Chemistry, 2025)
Brown rice planthopper (Nilaparvata lugens (Stål)) is a highly damaging pest of rice that has led to considerable losses in yields, increasing resistance to most conventional insecticides demands the adoption of eco-friendly chemical solutions. Cyperus rotundus L., a medicinal plant unaffected by N. lugens and reported to possess insecticidal properties, was selected for its potential to inhibit acetylcholinesterase (AChE), a key insect nervous system enzyme. Nine phytochemicals isolated from C. rotundus were evaluated through molecular docking, with quercetin (−8.9 kcal/mol), biochanin A (−8.7 kcal/mol), and cyperotundol (−8.1 kcal/mol) outperforming the positive control, carbofuran (−8.2 kcal/mol). The identified phytochemicals proved to have better binding affinity and complex stability, evidenced by the reduced values of RMSD/RMSF and more lasting interactions over 100 ns MD simulations compared to the positive control in both domain movement and binding stability. MMGBSA estimated favorable binding free energies (−67.06, −57.11, −71.07 kcal/mol) versus carbofuran (−36.84 kcal/mol). These findings suggest that C. rotundus phytochemicals are promising natural AChE inhibitors and potential candidates for sustainable N. lugens control. Their effectiveness implies the eco-friendly use of these natural compounds as a possible factor in the use of fewer and non-synthetic insecticides in pest control or integrated pest management.